Potential Confusion Between Value Investing and Fundamental Analysis Explored Through Piotroski F-Score - Murti, Nugroho Wisnu; Sugiri, Slamet (Universitas Muhammadiyah Surakarta, 2024)
This article addresses the potential confusion between fundamental analysis (FA) and value investing (VI) in stock analysis, particularly highlighting the over-reliance on financial ratios that can obscure their distinctions. It examines the role of the f-score, developed by Piotroski (2000) as a VI indicator, which is frequently misinterpreted within the context of FA. By analyzing its utilization in academic literature, the study examines to clarify how the f-score should be understood as a value investing tool and contribute to a clearer framework distinguishing the two approaches, thereby enhancing future research and educational efforts. This article employs bibliometric analysis. Our study finds that while the f-score is frequently associated with FA metrics, its intended purpose as a measure of VI more relevant. Additionally, we categorize value investing indicators into Single Value Investing Indicators (SVII) and Combined Value Investing Indicators (CVII), building upon the foundational works of Graham & Dodd (1934) and Lakonishok et al (1994). The findings suggest that Piotroski's f-score is more appropriately classified as a CVII and more effective in predicting abnormal returns when used within the value investing framework rather than fundamental analysis.